Research on the Application Risks of the Regulatory Mechanism of Embryonic Gene Editing Technology - Hu, Yuxiang (International Journal of Public Health and Medical Research, 2026)
This article takes one of the technical cores - regulatory mechanisms - as the starting point to discuss the direct risks such as off target and chimerism caused by the failure or imperfection of regulatory mechanisms; And analyze the potential medical risks, gene pool changes, ethical risks, and social evolution risks that this technology may bring from the perspectives of personal level, reproductive genetics, ethical and social aspects, and ecological evolution. This article also attempts to propose specific and feasible risk prevention and regulatory measures from the perspectives of technology, evaluation standards, laws and regulations, and social supervision, in order to benefit the cautious and rational use of embryo gene editing technology.